Diffuse Axonal Injury Associated with Chronic Traumatic Brain Injury: Evidence from T2*-weighted Gradient-echo Imaging at 3 T - Scheid, Rainer; Preul, Cristoph; Gruber, Oliver; Wiggins, Christopher; von Cramon, D. Yves (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Diffuse axonal injury is frequently accompanied by tissue tear hemorrhages. We examined whether high field strength T2*-weighted gradient-echo imaging performed during the chronic stage of traumatic brain injury may have advantages in the evaluation of diffuse axonal injury as compared with T1- and T2-weighted MR imaging.METHODS: Prospective MR imaging of 66 patients (age range, 17–57 years) was performed using a 3-T system 3 to 292 months (median, 23.5 months) after traumatic brain injury. T1-, T2-, T2*-hypointense and T2-hyperintense foci of 1- to 15-mm diameter were registered in 10 brain regions by two readers separately. Foci that appeared hypointense both on the T1- and T2- and/or on the T2*-weighted images were defined as traumatic microbleeds.RESULTS: For 46 (69.7%) of the patients, T2*-weighted gradient-echo imaging revealed traumatic microbleeds. Hyperintense foci were observed on the T2-weighted images of only 15 (22.7%) patients. T2*-weighted imaging showed significantly more traumatic microbleeds (P = .000) than did T1- and T2-weighted imaging. Interobserver agreement was strong (κ = 0.79, τ = 0.749, P = .000). For 14 (21.2%) of the patients, T2*-weighted gradient-echo imaging revealed traumatic microbleeds in the corpus callosum, whereas for only two (3%), hyperintense callosal lesions were seen on the T2-weighted images. Although a significant correlation existed between the total amount and callosal appearance of traumatic microbleeds and Glasgow Coma Scale scores (P = .000), no correlation existed with extended Glasgow Outcome Scale scores.CONCLUSION: T2*-weighted gradient-echo imaging at high field strength is a useful tool for the evaluation of diffuse axonal injury during the chronic stage of traumatic brain injury. Diffuse axonal injury-related brain lesions are mainly hemorrhagic. The relevance of diffuse axonal injury for long-term clinical outcome is uncertain.